2020
DOI: 10.2147/nss.s239706
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effects of Intraoperative Dexmedetomidine Use and Its Different Dose on Postoperative Sleep Disturbance in Patients Who Have Undergone Non-Cardiac Major Surgery: A Real-World Cohort Study</p>

Abstract: The study aimed to investigate the effects of intraoperative dexmedetomidine on postoperative sleep disturbance for different surgical patients and compare such effects between different dose of dexmedetomidine. Methods: A total of 7418 patients undergoing nine types of non-cardiac major surgeries were retrospectively studied. Patients were separated into DEX (dexmedetomidine) or Non-DEX (Non-dexmedetomidine) groups based on the use of dexmedetomidine during surgery. The patients who reported they could not fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
4
24
0
Order By: Relevance
“…In our study, the median (IQR) of age of the two groups was 59 (55,65) and 62 (56,67) years, so in consideration of concentration related adverse circulatory effects for elderly patients, we chose a 0.4 μg/kg infusion over 10 min, followed by a dose of 0.4 μg/kg/h to maintain the anesthesia. The similar low DEX infusion dosing could be found in many other studies [10,[29][30][31]. And our study also indicated that this dose of DEX continuous infusion did not increase the prevalence of bradycardia or hypotension, so we thought that our DEX dose was proper for safety evaluation.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, the median (IQR) of age of the two groups was 59 (55,65) and 62 (56,67) years, so in consideration of concentration related adverse circulatory effects for elderly patients, we chose a 0.4 μg/kg infusion over 10 min, followed by a dose of 0.4 μg/kg/h to maintain the anesthesia. The similar low DEX infusion dosing could be found in many other studies [10,[29][30][31]. And our study also indicated that this dose of DEX continuous infusion did not increase the prevalence of bradycardia or hypotension, so we thought that our DEX dose was proper for safety evaluation.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, the median (IQR) of age of the two groups was 59 (55,65) and 62 (56,67) years, so in consideration of concentration related adverse circulatory effects for elderly patients, we chose a 0.4 μg/kg infusion over 10 min, followed by a dose of 0.4 μg/kg/h to maintain the anesthesia. The similar low DEX infusion dosing could be found in many other studies 10,[30][31][32] . And our study also indicated that this dose of DEX continuous infusion did not increase the prevalence of bradycardia or hypotension, so we thought that our DEX dose was proper for safety evaluation.…”
Section: Discussionsupporting
confidence: 76%
“…As for the different time point, the DEX was used during the surgery for sedation in nine studies, 5 , 7 , 10 , 15–18 , 21 , 26 as an adjuvant for the regional block in one studies, 22 for postoperative analgesia in nine studies 8 , 12–14 , 19 , 23–25 , 27 and both in surgery and after surgery in eight studies. 9 , 11 , 20 And in 2 retrospective study 15 , 16 and one RCT 25 compared the effect of sleep quality of low dose of DEX (<0.2 μg/kg/h) and high dose (>0.2 μg/kg/h). As for other RCT studies, nine studies used DEX at a low dose and ten studies used DEX at a high dose.…”
Section: Resultsmentioning
confidence: 99%
“… 14 Five other studies found no significant benefit of DEX in reducing PONV. 10 , 16 , 18 , 19 , 24 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation